Assessing the values of living heritage sites in Kathmandu Valley: a community perspective. Issue 1 (4th February 2019) - K.C., Chandani; Karuppannan, Sadasivam; Sivam, Alpana
Abstract : Purpose: The purpose of this paper is to assess the heritage values of two case study sites in the Kathmandu Valley using a living heritage approach by emphasising the role of the core community. The core community in a living heritage site is the community that created the site and maintained it over centuries, and will continue to do so into the future while adapting to change. Understanding the value of a site is important for the conservation of heritage because values help shape decisions on conservation. Assessment of heritage values helps to identify the values associated with heritage sites. Design/methodology/approach: A case study approach was employed for the research. Questionnaire surveys were conducted with the core community and stakeholders. Surveys of the stakeholders looked for any difference in opinion between them and the core community. The empirical data were collected at two living heritage sites located in Kathmandu and Lalitpur in Nepal. Findings: The findings of the paper provide insights for the conservation of living heritage in the Kathmandu Valley. It shows how the community perceives and assesses the significance of heritage sites. It also shows the values considered important by the core community and stakeholders, and the values that have changed over the years. Aesthetic and architectural values were ranked high by the core community. Originality/value: The approach employed was adopted to assess heritage values by the core community. A living heritage site is dependent on the core community, so their perception of heritage value is important and should be the basis of conservation of living heritage. This paper provides a framework for conserving and managing heritage sites by the core community with support and guidance from wider community members and government authorities.